TERAPI BERMAIN MENDONGENG DAPAT MENURUNKAN TINGKAT KECEMASAN PADA ANAK USIA PRA SEKOLAH AKIBAT HOSPITALISASI - Kiyat W, Aji; Ani Y, Falasifah; Dias Utami, Khristina (Media Ilmu Kesehatan, 2014)
Background: Child is a unique individual and can also be sick with a greater risk so they need a hospitalization for diagnosing and treating the disease. Hospitalization can trigger anxiety. Reaction to anxiety can be shown by, among others: crying, being afraid, being agressive, curiosity, control-lost, confusion, refusing to eat, and refusing invasive treatment. Implementation of care for children can not be separated with the play therapy as an attempt to decrease anxiety, enhance cooperative behaviour, and stimulate the growth and development of children during their hospitalization. One of the recommended intervention is storytelling play therapy. Objective: Determine the influence of storytelling play therapy on the level of anxiety in pre-school children due to hospitalization at cempaka ward RAA Soewondo Pati Hospital. Methods: This study is quassy- experimental research design with a âone- group- before- afterâ (pretestposttest design) without control group. Total sampel in this study were 19 pre-school children using total sampling technique. Data collection was performed before and after the treatment using the instrument to know the level of anxiety that knew as HARS-A and statistic test which used is Wilcoxon signed rank test (Î±= 0,05). Result: The result of statistic analysis using Wilcoxon signed rank test shows significant p-value=0,000 (Î±= 0,05). It means storytelling play therapy has an influence on the level of anxiety in pre-school children due to hospitalization at Cempaka ward RAA Soewondo Pati Hospital. Conclusion: Storytelling play therapy has an effect to decrease the level of anxiety in pre-school children. Keywords: Play Therapy, Anxiety, Pre-school age, Hospitalization.